Pengaruh Beban Kerja, Lingkungan Kerja Dan gaya Kepemimpinan Terhadap Kinerja PT. Masaji Tatanan Kontainer Indonesia Cabang Medan Belawan - Laily Arafah; Eka Purnama sari (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine the influence of workload, work environment and leadership style on employee performance. This research uses a quantitative method with data collection techniques, questionnaires and interviews. The number of samples in this study was as many as respondents. Drawing the number of samples using the Total Sampling technique. Data management uses SPSS version 25 software. Based on research, it shows that Work Load is tcount 2.337 > ttable 2.016, so Workload partially has a significant effect on Employee Performance. In the work environment, the value obtained is tcount 3.016 > ttable 2.016, so the work environment partially has a significant effect on employee performance. For Leadership Style, the value obtained is -877< ttable 2.016, so Leadership Style partially has no significant effect on Employee Performance. Based on the Fcount value = 7.542 while the Ftable value = at a = 0.05 with n = 47, the Ftable value is obtained. From these results it is known that Fcount > Ftable is 7.542 > 2.82. So it can be concluded that Workload, Work Environment, and Leadership Style together influence Employee Performance at PT. Masaji Tatanan Kontainer Indonesia Cabamg Medan Belawan.